Targeting the Salience Network: A Mini-Review on a Novel Neuromodulation Approach for Treating Alcohol Use Disorder - Padula, Claudia B.; Tenekedjieva, Lea-Tereza; McCalley, Daniel M.; Al-Dasouqi, Hanaa; Hanlon, Colleen A.; Williams, Leanne M.; Kozel, F. Andrew; Knutson, Brian; Durazzo, Timothy C.; Yesavage, Jerome A.; Madore, Michelle R. (Frontiers in Psychiatry, 2022)
Alcohol use disorder (AUD) continues to be challenging to treat despite best available interventions, with two-thirds of individuals going on to relapse by one year after treatment. Recent advances in the brain-based conceptual framework of addiction have allowed the field to pivot into a neuromodulation approach to intervention for these devastative disorders. Small trials of repetitive transcranial magnetic stimulation (rTMS) have used protocols developed for other psychiatric conditions and applied them to those with addiction with modest efficacy. Recent evidence suggests that a TMS approach focused on modulating the salience network, a circuit at the crossroads of large-scale networks associated with AUD, may be a fruitful therapeutic strategy. The anterior insula or dorsal anterior cingulate cortex may be particularly effective stimulation sites given emerging evidence of their roles in processes associated with relapse.